2021
DOI: 10.30543/10-1(2021)-11
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Personality Traits as the Antecedents of Workplace Bullying

Abstract: There is an ample body of knowledge showing significant association between five factor model (FFM) of personality traits and workplace bullying, yet exploring cause-and-effect relationship between them is still under addressed. To address this issue, current study has analyzed personality traits of Five-Factor Model as a potential antecedent of workplace bullying and its three sub-facets (verbal bullying, social bullying and physical bullying). Study analyzed responses of 266 respondents to draw inferences. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…The result aligns with a study conducted by Munir et al (2021), which also found a significant impact of personality traits such as extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience on workplace bullying. The study's consistent findings strengthen the understanding that individual characteristics, specifically dispositional factors, such as job insecurity, job autonomy, stressful work situations and boredom play a crucial role in shaping bullying behaviors in the workplace, including the unique context of law enforcement.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The result aligns with a study conducted by Munir et al (2021), which also found a significant impact of personality traits such as extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience on workplace bullying. The study's consistent findings strengthen the understanding that individual characteristics, specifically dispositional factors, such as job insecurity, job autonomy, stressful work situations and boredom play a crucial role in shaping bullying behaviors in the workplace, including the unique context of law enforcement.…”
Section: Resultssupporting
confidence: 91%
“…A study by van der Westhuizen (2021) discovered that people who score highly on openness tend to dislike routine experiences. Munir et al `(2021) found that those scoring high on this trait become non-traditional because of a broad diversity of activities and preclude predictable stances. The fifth factor as researched by Grohol (2019) is conscientiousness which is defined as an individual's ability to control their instincts and participate in goal-oriented conduct, well-organised, disciplined, thoughtful, cautious, and meet objectives.…”
Section: Dispositional Factors and Situational Factors Of Workplace B...mentioning
confidence: 99%